Concise synthesis of the core structure of madreporanone by Rh-catalyzed [3+2] cycloaddition. Issue 12 (22nd March 2019) - Long, Rong; Yang, Zhen
Abstract: A model study toward total synthesis of madreporanone, a novel diterpene isolated from Azorella madreporica, was investigated. The [3.3.0] bicyclic core of madreporanone bearing a cis -configured isopropyl group and two vicinal quaternary carbon centers was stereoselectively constructed via an intramolecular Rh-catalyzed [3 + 2] cycloaddition in a single step. Graphical abstract: Image 1